PENGARUH PENGGUNAAN BOOKLET SISTEM PENCERNAAN TERHADAP HASIL BELAJAR KELAS XI MAN 1 BUKITTINGGI - Mustika Lara; S. Syamsurizal (LPPM Universitas Cipta Mandiri, 2024)
The aim of this research is to determine the effect of the Digestive System Booklet on Learning Outcomes for Class Xi Man Phase 1 Bukittinggi. This research is an experimental research with a post-test only control group design method, with a population of 108 and a sample size of two classes consisting of 36 students of class XI phase f1.5 (experimental class) and 36 students of class XI phase f1.4 class (control). The sampling used was cluster random sampling. Data collection uses a questionnaire. Data were analyzed using t-test. The research results show that there is a significant impact on the use of booklet media on student learning outcomes with a t value of 5.129 with sig. 0.001 or smaller than 0.5. This is because booklet media has several advantages, namely its smaller size so students can carry it everywhere. Apart from that, the booklet media is composed of interesting pictures and the concept of the material is presented based on learning problems found in the environment around the students so as to encourage students' curiosity and attract students' attention to be active and enthusiastic in learning and help students understand the learning material verbally and visually. based on concrete things that students often encounter. Based on this, it can be concluded that there is an influence of the use of the digestive system booklet on the learning outcomes of class xi phase f students at MAN 1 Bukittinggi. Keywords: Influence, Booklet, Learning Results